2016
DOI: 10.1371/journal.pone.0157480
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Intramammary Escherichia coli Challenge on Liver and Mammary Transcriptome and Cross-Talk in Dairy Cows during Early Lactation Using RNAseq

Abstract: Our objective was to identify the biological response and the cross-talk between liver and mammary tissue after intramammary infection (IMI) with Escherichia coli (E. coli) using RNAseq technology. Sixteen cows were inoculated with live E. coli into one mammary quarter at ~4–6 weeks in lactation. For all cows, biopsies were performed at -144, 12 and 24 h relative to IMI in liver and at 24 h post-IMI in infected and non-infected (control) mammary quarters. For a subset of cows (n = 6), RNA was extracted from bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 60 publications
0
28
0
Order By: Relevance
“…Interestingly, all of the disease categories associated with the miRNAs identified in this study included liver diseases (hepatocellular carcinoma in the cancer category, HEV in the infection category, and hepatitis B in the immune category). Gene expression profiling of liver tissues from dairy cows treated with intramammary Escherichia coli or lipopolysaccharide confirmed that the liver plays a major role in the acute‐phase response in E. coli ‐induced mastitis and that hepatic failure can be caused by mastitis or metritis , suggesting potential crosstalk between the liver and the mastitic mammary gland. HEV is the causative agent of hepatitis E, and anti‐HEV antibodies can be detected in humans and domestic and wild animals .…”
Section: Discussionmentioning
confidence: 90%
“…Interestingly, all of the disease categories associated with the miRNAs identified in this study included liver diseases (hepatocellular carcinoma in the cancer category, HEV in the infection category, and hepatitis B in the immune category). Gene expression profiling of liver tissues from dairy cows treated with intramammary Escherichia coli or lipopolysaccharide confirmed that the liver plays a major role in the acute‐phase response in E. coli ‐induced mastitis and that hepatic failure can be caused by mastitis or metritis , suggesting potential crosstalk between the liver and the mastitic mammary gland. HEV is the causative agent of hepatitis E, and anti‐HEV antibodies can be detected in humans and domestic and wild animals .…”
Section: Discussionmentioning
confidence: 90%
“…The approaches applied for RNA-Seq bioinformatics analyses have been previously described49. Briefly, the indices of the bovine reference genome (UMD3.1) were first built using the Build-Index function implemented in the Rsubread package51.…”
Section: Methodsmentioning
confidence: 99%
“…An important role of the liver and the liver and mammary crosstalk during mastitis was uncovered by transcriptomic works in dairy cows [42] [13]. …”
Section: Resultsmentioning
confidence: 99%